DETERMINAN PENGGUNAAN CROWDFUNDING BERBASIS DONASI - Gusi Putu Lestara Permana; Dewa Ayu Bintang Rahayuni (Jurnal Aplikasi Akuntansi, 2023)
The purpose of this study is to understand the use of donation-based crowdfunding services from the user dimension. The location of this study was in the Bali region with a sample of 95 people who met the sample criteria. The collected data were analyzed using Partial Least Square (PLS) with the analysis method using the measurement evaluation model (outer model) and structural evaluation model (inner model). In this study, it can be concluded that the variables used, namely perceived security, corporate accountability, social motivation, and reputation encourage users to use donation-based crowdfunding, this is related to the Theory of Planned Behavior, in this case encouraging interest in using it on the user's side.